2011
DOI: 10.2527/jas.2011-3954
|View full text |Cite
|
Sign up to set email alerts
|

An increased feed intake during early pregnancy improves sow body weight recovery and increases litter size in young sows1

Abstract: This study evaluated the effect of feeding level and protein content in feed in first- and second-parity sows during the first month of gestation on sow BW recovery, farrowing rate, and litter size during the first month of gestation. From d 3 to 32 after the first insemination, sows were fed either 2.5 kg/d of a standard gestation diet (control, n = 49), 3.25 kg/d (+30%) of a standard gestation diet (plus feed, n = 47), or 2.5 kg/d of a gestation diet with 30% greater ileal digestible AA (plus protein, n = 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 31 publications
4
14
0
1
Order By: Relevance
“…Nor were there any treatment effects on litter weight at birth and weaning, which is in accordance with the study by Le Cozler et al (1999b). Hoving et al (2011) compared the reproductive performance of gilts after they had been given a standard gestation diet (2.5 kg/d), a plus feed diet (3.25 kg/d of gestation diet) or an extra 30% of protein in the diet the first month after service. They found that the plus feed treatment, which is similar to the higher dietary energy level during mid-gestation in our study, resulted in an average of 2 more piglets without decreasing the average piglet birth weight.…”
Section: Discussionsupporting
confidence: 69%
“…Nor were there any treatment effects on litter weight at birth and weaning, which is in accordance with the study by Le Cozler et al (1999b). Hoving et al (2011) compared the reproductive performance of gilts after they had been given a standard gestation diet (2.5 kg/d), a plus feed diet (3.25 kg/d of gestation diet) or an extra 30% of protein in the diet the first month after service. They found that the plus feed treatment, which is similar to the higher dietary energy level during mid-gestation in our study, resulted in an average of 2 more piglets without decreasing the average piglet birth weight.…”
Section: Discussionsupporting
confidence: 69%
“…), which may stimulate embryo development and progesterone production during early gestation (Hoving et al. ), however, it is presently unclear why HMB may increase the survival of fetal pigs at birth, and this aspect should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Another important observation was that maternal HMB treatment significantly decreased the rate of stillborn piglets. In this respect, some studies have reported that dietary supplementation of HMB may increase the activity of IGF-1 (Tatara et al 2007), which may stimulate embryo development and progesterone production during early gestation (Hoving et al 2011), however, it is presently unclear why HMB may increase the survival of fetal pigs at birth, and this aspect should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found that relatively high feeding levels during early pregnancy may be beneficial for litter size in sows (e.g. Sørensen and Thorup 2003; Hoving et al. 2011), although the physiological mechanism has not been elucidated.…”
Section: The Pregnant Sowmentioning
confidence: 99%